2021
DOI: 10.3390/ijerph18094563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Health-Related Quality of Life in Adolescents and Children: A Systematic Review

Abstract: The aim of the present systematic review was to assess and provide an up-to-date analysis of the impact of coronavirus disease 2019 (COVID-19) pandemic on the health-related quality of life (HRQoL) of children and adolescents. Thus, an electronic search of the literature, in two well-known databases (PubMed and Web of Science), was performed until February 2021 (without date restriction). PRISMA guideline methodology was employed and data regarding the HRQoL were extracted from eligible studies. Articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(177 citation statements)
references
References 61 publications
16
153
0
8
Order By: Relevance
“…Young adult females have reported a higher severity of symptoms of depression and higher levels of psychological distress (including anxiety) than their young adult male peers in Germany, Japan, and Saudi Arabia [19,20,44]. In addition, a systematic review also found that the COVID-19 pandemic had negatively impacted females psychological and mental health, more than males [45]. Similarly, female students at the University of Zaragoza in Spain reported more stress due to the pandemic [46].…”
Section: Discussionmentioning
confidence: 99%
“…Young adult females have reported a higher severity of symptoms of depression and higher levels of psychological distress (including anxiety) than their young adult male peers in Germany, Japan, and Saudi Arabia [19,20,44]. In addition, a systematic review also found that the COVID-19 pandemic had negatively impacted females psychological and mental health, more than males [45]. Similarly, female students at the University of Zaragoza in Spain reported more stress due to the pandemic [46].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from studying at school, children undertake many additional activities, such as horse riding, swimming, dancing, learning foreign languages, etc. The limitation of these activities also limited contact with friends, which significantly increased efforts to maintain relationships through social media and various types of communicators [ 8 ]. It significantly influenced their health, including nutrition, physical exercise, sleep, and social functioning, increasing their media use [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that physical fitness and moderate-intensity training also have reverse correlations with risks of disease and premature fatality [15,16], which can be that immune response function and improved types of immune markers can be increased by exercise in some diseases. These diseases can include low-grade inflammation, hypertension, stroke, osteoporosis, cancer (e.g., colon, lung, stroke, and breast), chronic infectious disease, metabolic syndrome, cardiovascular disease, type 2 diabetes mellitus, cognitive impairment and obesity [6,17,18].…”
Section: Dear Editormentioning
confidence: 99%
“…It is safe to exercise during the COVID-19 epidemic in healthy individuals, taking the necessary precautions, such as exercising at home. After COVID-19 disease, due to the spread of infection, the patients will not be able to exercise [ 16 , 19 ]. COVID-19 mortality is on average 2%, whereas most people are treated after a specified period.…”
Section: Dear Editormentioning
confidence: 99%